Penerapan Metode Framework for the Applications of System Thinking dalam Sistem Pencari Pekerjaan - Rima Tamara Aldisa; Puspa Ayu Soleha (STMIK Budi Darma, 2023)
In the digital era and the development of information technology, it is necessary to have a website to make it easier to carry out activities and find sources of information and knowledge quickly. Information about job vacancies is an important thing that is needed and needed by people who want to get a suitable job. The source of information that is easy and fast makes updating information about job vacancies every day. Designing a web-based job search information system which is built on an initial display menu, a job type menu, namely all types of vacant position fields along with the name of a limited liability company that is in need of employees and also the location of the company. Using the Framework For The Applications Of System Thinking can assist in software development which is carried out in several ways in stages. The Framework For The Applications Of System Thinking in its use is able to make decisions in changing and developing software according to the conditions of the situation. By testing the system with blackbox testing to further ensure that all system displays are functioning properly and running properly. The result of this system is a website-based job search information system that has a search menu, position field type menu, location map according to google maps.